Effect of Dietary Supplementation of Choline from Different Sources on Performance and Economics of Commercial Broiler Chicken - 1; 2; Savaliya, Fulabhai P.; Patel, Atul B.; Ghasura, Arman S.; Patel, Nishant M.; Rajpura, Rais M. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
An experiment was conducted to investigate the effect of dietary supplementation of choline from different sources on the performance and economics of commercial broiler chicken. Day old broiler chicks (Vencobb, n=216) were randomly distributed into nine experimental groups with four replicates of six birds each. The experimental groups (T1 to T9) were fed with diet containing choline chloride 60% @ 1000 g/ton, 750 g/ton, and 500 g/ton feed in T1 (Control), T2, and T3 ration. Similarly, herbal choline @ 1000 g/ton, 750 g/ton and 500 g/ton feed was given in T4,5,6 ration, and phosphatidylcholine @ 1000 g/ton 750 g/ton and 500 g/ton feed-in T7,8,9 ration, respectively. The trial was carried out in deep litter pen for 42 days. During the whole experiment, the mortality pattern of the birds was within the permissible limits and revealed no adverse effects of feeding choline from different sources in diet. The study results indicated that the supplementation of choline chloride 60% @1000 g/ton feed (Control group) showed higher body weight and body weight gain compared to other rations. Total feed consumption and feed conversion ratio of birds fed with treatment rations supplemented with different choline sources were at par among the rations. The return over feed cost was highest in broilers fed a diet with choline chloride 60 % @ 1000 g/ton feed.